The effect of maximal anaerobic capacity training on developing speed and long jump performance in under 20 years old - Hussein, L. Ali Abdul Amir; عطية, م. محمد بجاي; Ajrash, L. Games Muhammad Khudair; Assi, Asst.L. Ali Sobhi (Sulaimani Journal for Humanities, 2026)
The first chapter of the research contained the introduction and the importance of the research, in which the continuous scientific development of all different sciences was identified, including the science of sports training, which has received the attention of different sciences, which has helped in discovering many training methods. These methods helped athletes improve their performance, particularly in athletics. The long jump competition was also identified, along with the training methods that help improve performance in this competition. The importance of the research lies in selecting and developing an effective training method to improve performance in the long jump competition for those under 20 years old by developing specific exercises to enhance the speed ability of jumpers and the effect of these exercises on improving performance in this competition. As for the research problem, the level of achievement in athletics has recently declined in our beloved country, especially the level of achievement in the long jump competition for those under 20 years old. This decline is due to weakness in many important physical attributes and physical abilities, namely (explosive ability - speed ability), which play a major role in improving performance in this competition. The research aims to use specific exercises to develop speed ability in the research sample, to identify the effect of these specific exercises on speed ability in the research sample, and to identify the effect of these specific exercises on long jump performance in the research sample for those under 20 years old. As for the research hypotheses, there are statistically significant differences between the pre-test and post-test for the speed ability variable, in favor of the post-test. There are statistically significant differences between the pre-test and post-test in long jump performance among the under-20 year olds in the research sample, favoring the post-test. There are also statistically significant differences between the experimental and control groups, favoring the experimental group, in the research variables. The researchers defined the research scope: the human scope, which was the national under-20 jumpers; the temporal scope, which was from December 21, 2024, to February 28, 2025; and the spatial scope (the Ministry of Youth and Sports Center – the College of Physical Education and Sports Sciences Stadium – Al-Jadriya). In the second chapter, the researchers described the research methodology and its field procedures. This chapter included a description of the research methodology used by the researchers, which was the experimental method. It also included the field experiment procedures, which involved the sample, the instruments used, the pre-tests, the post-tests, and the statistical methods. The researchers selected a sample of national team jumpers and divided them into two groups (control and experimental). They were subjected to tests developed by the researchers, and then the experimental group underwent a special training program. Afterward, the researchers conducted the post-tests. Appropriate statistical methods were used to compare the pre-tests and post-tests. Chapter Three included a presentation of the results obtained from the pre-tests and post-tests that were applied to the research sample, and scientific results were reached and then discussed.